Adaptive simulations to pressure distribution for creeping motion of Carreau nanofluid with variable fluid density effects: Physiological applications. (1st July 2022) - Ibrahim, M.G.
Highlights: The theoretical suggestion of variable fluid density gives effective and practical results for pressure distribution. The high values of non-constant fluid density parameters enforce the pressure gradient and pressure rise in a cervical canal, which help sperms to be more active in ovum fertilization. Reynolds and Froude numbers have two opposite behavior on pressure gradient profile. Dual role phenomena visualized on Weissenberg number behavior on pressure rise distribution. High values of ∊ angle causes to a growing in pressure rise in all pumping regions. AST is an effective technique for solving a highly nonlinear problem without perturbation techniques. Abstract: The density of sperms via the cervical canal has an essential vital role in enhancing the pregnancy processes for organisms. Hence, this study aims to investigate a new theoretical suggestion for the variable density effects on the creeping flow of a non-Newtonian nanofluid in the cervical canal. The density is supposed to vary with the fluid temperature and concentration. The fluid is mathematically designated with a system of PDEs. This system of a physical model is simplified/streamlined using appropriate transformation ( δ ≪ 1 ) to an ODEs. A resulting model is analytically recurrences by adaptive shooting technique (AST). Results for pressure gradient and pressure rise distributions are outlined/sketched. Furthermore, streamlines showed in a contoured frame. Validation of results was confirmed through a comparison with Noreen et al [3] . Outgrowths state that high values of concentration and temperature-dependent density parameters enforce the pressure gradient and pressure rise in a cervical canal, which helps sperms to be more active in ovum fertilization.